IMPACT OF FLASH SALE ON GENDER - Sreenidhi. T. S , Anantha Padmanabhan. R , Shagavarthini. S. K , Jenita Ooviya. J (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Flash sales is one of the most anticipated and loved sales during the festival seasons like Diwali and Pongal in India. India is a country with lot of needs and necessity considering the population. Not every day we tend to get products at a good discounted price and this is where flash sales make us wait for them and get the products during their sale. This paper will discuss about four important factors about flash sales and which gender involve a lot during the flash sale.